جهود مكتب مفتي الولايات الفيدرالية بماليزيا في خدمة الحديث - Shumsudin Yabi; Nur Afifi bin Alit; Aminudin Basir @Ahmad; Muhammad Yofef Niteh; Fadlan bin Mohd Othman; Akila Mamat (Universiti Sains Islam Malaysia, 2024)
Date: 9 September 2021 Platform: MSTeams, USIM Nilai, Negeri Sembilan, Malaysia.